TRANSFORMATIVE MUTUAL PUBLIC RELATIONS IN CHARACTER EDUCATION: A SYNERGISTIC APPROACH BETWEEN SCHOOLS AND FAMILIES - Holifah, Holifah; Mundiri, Akmal; Sholehah, Baitus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the application of the concept of mutual public relations in character education at Nurul Jadid Middle School, focusing on the synergy between school and family. Mutual Public Relations, which involves the cooperation of two or more parties in building mutually supportive relationships, is applied in this context to strengthen student character formation through active collaboration between the school, parents, and foster carers. This research found that open communication and parental involvement in various school activities can strengthen character values such as discipline, responsibility, and empathy. In addition, the role of foster carers as a liaison between family and school has also been proven to increase the effectiveness of character education by providing consistent support and feedback. The synergy between these three parties creates a more holistic environment for students' moral development, where character values are taught at school and applied in daily life at home and in the dormitory. It is hoped that these findings can provide new insights for developing a more integrative and sustainable character education model through mutual public relations in other schools.